Implementation of the Influence of Marketing Mix Strategy (4P) on Increasing Sales of Bumi Petung Residence Houses in Penajam Paser Utara Regency - Mujahid; St. Rukaiya; Gustin Winaria (Universitas Muhammadiyah Palu, 2024)
This study aims to analyze the influence of product, price, location, promotion, and variables from the marketing mix strategy that most dominantly affect the sales of Bumi Petung Residence houses in Penajam Paser Utara Regency. The research was conducted in Penajam Paser Utara Regency, East Kalimantan, Indonesia, focusing on the Bumi Petung Residence housing project. Both qualitative and quantitative data were utilized, including interviews, observations, and secondary data sources. The research population consisted of 172 consumers who had purchased houses in Bumi Petung Residence until 2023, with a sample of 155 respondents. Regression analysis was employed to determine the significance of marketing variables' influence. Based on the research findings, it is concluded that product and price are not significant factors affecting house sales in Bumi Petung Residence. However, location significantly influences sales, indicating the attractiveness of the property's location. Promotion also has a significant impact on increasing buyer interest and market reach. Therefore, a more focused marketing strategy, especially on promotion and location, is crucial for overall property sales improvement.